Topical Methotrexate for Treatment of Psoriasis: Formulation and Clinical Implications. - Jabur, Murtadha S.; Ghazal, Mohammed R. I.; Al-Hamamy, Hayder R. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: To test effectiveness and safety of topical methotrexate 0.5%gel and to introduce new formula of methotrexate gel using suitable media for delivery.Patients and Methods: The clinical work was performed at the Department of Dermatology and Venereology in Baghdad Teaching Hospital during the period from January 2008 to October 2008. While preparation of formula was performed in the laboratories of the Department of Pharmacology- College of Medicine-University of Baghdad. Patients were divided in to two groups according to the type of treatment, group (I) 32 patients treated with methotrexate 0.5% gel and group(II) (placebo group) included 33 patients treated with placebo gel.Results: A total of 65 patients with limited plaque psoriasis were included in this study. For the MTX group the mean PASI score before treatment was 7.07 while at 2, 4, 6 and 8 weeks treatment, it was decreased to 5.17, 3.93, 3.07 and 2.35 respectively. At eight weeks treatment 25(78%) patients achieved good response (reduction in PASI score 50%), while 5(15.6%) patients achieved partial response (reduction in PASI score 25-49%) and 2(6.25%) patients had poor response (reduction in PASI score< 25%). For placebo group the pretreatment mean PASI score was 7.12 and after 2, 4, 6 and 8 weeks treatment it became 6.32, 6.07, 5.99 and 6.2 respectively. Clinically the response of the patients to placebo gel at 8 weeks treatment was partial in 10(30.3%) patients and poor in 23(69.7%) patients while no patients achieved good response. Conclusions: MTX 0.5% gel is effective treatment option for plaque psoriasis and also appears to be safe treatment since side effects were transient, limited and reduced with continuation of therapy.